Selective intracardiac sympathetic denervation acutely modulates left ventricular control. (19th May 2022) - Kahle, AK; Klatt, N; Jungen, C; Dietenberger, A; Kuklik, P; Muenkler, P; Willems, S; Nikolaev, V; Scherschel, K; Meyer, C
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): German Centre for Cardiovascular Research (DZHK) Background: The sympathetic nervous system plays an integral role in cardiac physiology. Neuromodulation is emerging as a treatment option for ventricular arrhythmias, but selective intracardiac approaches are rare. Sympathetic nerve fibers innervating the left ventricle have been demonstrated to be amenable to transvenous catheter stimulation along the coronary sinus (CS). Purpose: The aim of the present study was to modulate left ventricular control by selective sympathetic denervation using epicardial or standard catheter ablation for intracardiac axotomy at the level of the CS. Methods: First, the impact of epicardial CS ablation on cardiac electrophysiology was studied in a Langendorff model of murine hearts (n=10 each, ablation and control). Second, the impact of transvenous, anatomically-driven axotomy by catheter-based radiofrequency ablation along the CS was evaluated in a healthy ovine in vivo model (n=8) before and during left stellate ganglion stimulation (LSGS). Results: CS ablation for intracardiac sympathetic axotomy prolonged epicardial ventricular refractory period (VRP) without (41.8±8.4 ms vs. 53.0±13.5 ms; P=0.0487) and with beta1-2-adrenergic receptor blockade (47.8±2.8 ms vs. 73.1±5.0 ms; P=0.0009) and enhanced the increasing effect of beta1-2-adrenergic receptor blockade on epicardial VRP (∆VRP 6.3±7.0 ms vs. 20.0±7.5 ms; P=0.0045) in mice (Figure, A). Mean epicardial wave propagation velocity in the left ventricle was faster in ablated hearts than in controls (1.13±0.05 m/s vs. 1.00±0.02 m/s; P=0.0463), but did not differ in the right ventricle (1.15±0.05 m/s vs. 1.20±0.08 m/s; P=0.7938). Transvenous catheter ablation of the CS reduced systolic (SBP, 57.7±5.0 mmHg vs. 46.9±3.6 mmHg; P=0.0428) and diastolic blood pressure (DBP, 35.5±3.0 mmHg vs. 26.7±1.8 mmHg; P=0.0106) and diminished the blood pressure increase during LSGS in sheep (∆SBP 21.9±3.8 mmHg vs. 10.5±4.2 mmHg; P=0.0234; ∆DBP 9.0±1.9 mmHg vs. 3.0±1.2 mmHg; P=0.0391) (Figure, B, C). Cycle length remained unchanged by LSGS, both before (baseline 653.2±20.6 ms vs. LSGS 627.8±27.5 ms; P=0.2309) and after CS ablation (baseline 734.8±24.2 ms vs. LSGS 746.2±37.3 ms; P=0.7145). Conclusions: Anatomically-driven axotomy targeting nerve fibers along the CS enables selective intracardiac sympathetic denervation resulting in acute modulation of left ventricular control.